Efektivitas Penggunaan Video Edukasi Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Di SD - Mamonto, Rubi Alamsyah; Muzaini, M Choirul; Supriadi, Muhamad; Prastowo, Andi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to reveal the effectiveness of educational videos in increasing student learning outcomes in social studies subjects in elementary schools. This study used a qualitative research method. The research was carried out on October 3, 2022, using interview techniques, while data analysis techniques were carried out descriptively. The results of the analysis show that there is an increase in student learning outcomes by using educational video media in the learning process. In the classical pre-test students who completed only 14.7% and the average score was only 60.29%, while in the classical post-test students who completed 80.29% and obtained an average score of 84.2%, this study asked selesei, based on the results of data analysis it can be concluded that educational videos are effective for improving student learning outcomes in social studies subjects.